The Abrupt and Persistent Decline in Recruitment Success in Northeast Arctic Cod: A Review of Probable Causes - Edda Johannesen; Geir Ottersen; Florian Berg; Bjarte Bogstad; Padmini Dalpadado; Côme Denechaud; Elena Eriksen; Maria Fossheim; Håvard Guldbrandsen Frøysa; Torild Johansen; Knut Korsbrekke; Even Moland; et al. (Fish and Fisheries, 2026)
Most of the previously large cod stocks in the North Atlantic are depleted to very low levels. A notable exception has been the Northeast Arctic cod inhabiting the Barents Sea. This cod stock reached a record high level around 2013, but since then has declined sharply, with older fish being fished out and few new recruits entering the stock. More specifically, since 2006 the average recruitment at age 3 per unit spawning stock biomass has dropped to a very low level. Here we review recent literature and data to evaluate potential causes of poor recruitment. We find that in most years the large spawning stock was successful in producing offspring up to the 0‐group stage, but the survival thereafter was reduced—leading to few recruits into the fishable stock. Evidence points to consequences of northwards shifts of spawning locations, reduced inflow of Calanus and density dependent factors influencing pre‐recruit survival at times when the spawning stock was at a record high level. However, large uncertainties in the causes of recruitment failure remain at a time when the Barents Sea ecosystem is experiencing unprecedented warming. A precautionary measure to avoid further decline and potential stock collapse in the current situation is to lower fishing pressure and improve management by setting reference points based on the recent period with low productivity. Including demographic characteristics like age diversity as explicit management targets to ensure spatial and temporal spread in spawning should be a goal for future method development.

Latitudinally distinct stocks of Atlantic cod face fundamentally different biophysical challenges under on‐going climate change - Olav Sigurd Kjesbu; Maud Alix; Anne Britt Sandø; Espen Strand; Peter J. Wright; David G. Johns; Anders Thorsen; C. Tara Marshall; Kjell Gunnar Bakkeplass; Frode B. Vikebø; Mari Skuggedal Myksvoll; Geir Ottersen; et al. (Fish and Fisheries, 2023)
The reproductive success of marine ectotherms is especially vulnerable in warming oceans due to alterations in adult physiology, as well as embryonic and larval survival prospects. These vital responses may, however, differ considerably across the species' geographical distribution. Here we investigated the life history, focusing on reproductive ecology, of three spatially distant populations (stocks) of Atlantic cod ( Gadus morhua , Gadidae) (50–80° N), in the Irish/Celtic Seas‐English Channel Complex, North and Barents Seas, under past and projected climate. First, experimental tracking of spawning behaviour evidenced that the ovulation cycle is highly distressed at ≥9.6 (±0.25)°C ( T up ). This knife‐edge threshold resulted in erratic spawning frequencies, whereas vitellogenin sequestration remained unaffected, indicating endocrine rather than aerobic scope constraints. Cod in the Celtic Sea‐English Channel are, therefore, expected to show critical stock depensation over the next decades as spawning grounds warm above T up , with Irish Sea cod subsequently at risk. Second, in the relatively cooler North Sea, the northward retraction of Calanus finmarchicus (Calanidae) and Para‐Pseudocalanus spp. (Clausocalanidae) (1958–2017) limit cod larvae feeding opportunities, particularly in the southernmost subarea. However, the contrasting increase in Calanus helgolandicus (Calanidae) does not counteract this negative effect, likely because cod larvae hatch ahead of its abundance peaks. Overfishing again comes as a twin effect. Third, in the still relatively cold Barents Sea, the sustainably harvested cod benefit from improved food conditions in the recent ice‐free polar region but at the energetic cost of lengthier and faster spawning migrations. Consequently, under climate change local stocks are stressed by different mechanistic factors of varying management severity.

Successive extreme climatic events lead to immediate, large‐scale, and diverse responses from fish in the Arctic - Bérengère Husson; Sigrid Lind; Maria Fossheim; Hiroko Kato‐Solvang; Mette Skern‐Mauritzen; Laurène Pécuchet; Randi B. Ingvaldsen; Andrey V. Dolgov; Raul Primicerio (Global Change Biology, 2022)
The warming trend of the Arctic is punctuated by several record‐breaking warm years with very low sea ice concentrations. The nature and reversibility of marine ecosystem responses to these multiple extreme climatic events (ECEs) are poorly understood. Here, we investigate the ecological signatures of three successive bottom temperature maxima concomitant with surface ECEs between 2004 and 2017 in the Barents Sea across spatial and organizational scales. We observed community‐level redistributions of fish concurrent with ECEs at the scale of the whole Barents Sea. Three groups, characterized by different sets of traits describing their capacity to cope with short‐term perturbations, reacted with different timing and intensity to each ECE. Arctic species co‐occurred more frequently with large predators and incoming boreal taxa during ECEs, potentially affecting food web structures and functional diversity, accelerating the impacts of long‐term climate change. On the species level, responses were highly diversified, with different ECEs impacting different species, and species responses (expansion, geographical shift) varying from one ECE to another, despite the environmental perturbations being similar. Past ECEs impacts, with potential legacy effects, lagged responses, thresholds, and interactions with the underlying warming pressure, could constantly set up new initial conditions that drive the unique ecological signature of each ECE. These results highlight the complexity of ecological reactions to multiple ECEs and give prominence to several sources of process uncertainty in the predictions of climate change impact and risk for ecosystem management. Long‐term monitoring and studies to characterize the vertical extent of each ECE are necessary to statistically link demersal species and environmental spatial–temporal patterns. In the future, regular monitoring will be crucial to detect early signals of change and understand the determinism of ECEs, but we need to adapt our models and management to better integrate risk and stochasticity from the complex impacts of global change.

Highly mixed impacts of near‐future climate change on stock productivity proxies in the North East Atlantic - Olav Sigurd Kjesbu; Svein Sundby; Anne Britt Sandø; Maud Alix; Solfrid Sætre Hjøllo; Maik Tiedemann; Mette Skern‐Mauritzen; Claudia Junge; Maria Fossheim; Cecilie Thorsen Broms; Guldborg Søvik; Fabian Zimmermann; et al. (Fish and Fisheries, 2022)
Impacts of climate change on ocean productivity sustaining world fisheries are predominantly negative but vary greatly among regions. We assessed how 39 fisheries resources—ranging from data‐poor to data‐rich stocks—in the North East Atlantic are most likely affected under the intermediate climate emission scenario RCP4.5 towards 2050. This region is one of the most productive waters in the world but subjected to pronounced climate change, especially in the northernmost part. In this climate impact assessment, we applied a hybrid solution combining expert opinions (scorings)—supported by an extensive literature review—with mechanistic approaches, considering stocks in three different large marine ecosystems, the North, Norwegian and Barents Seas. This approach enabled calculation of the directional effect as a function of climate exposure and sensitivity attributes (life‐history schedules), focusing on local stocks (conspecifics) across latitudes rather than the species in general. The resulting synopsis (50–82°N) contributes substantially to global assessments of major fisheries (FAO, The State of World Fisheries and Aquaculture, 2020), complementing related studies off northeast United States (35–45°N) (Hare et al., PLoS One, 2016, 11, e0146756) and Portugal (37–42°N) (Bueno‐Pardo et al., Scientific Reports, 2021, 11, 2958). Contrary to prevailing fisheries forecasts elsewhere, we found that most assessed stocks respond positively. However, the underlying, extensive environmental clines implied that North East Atlantic stocks will develop entirely different depending upon the encountered stressors: cold‐temperate stocks at the southern and Arctic stocks at the northern fringes appeared severely negatively impacted, whereas warm‐temperate stocks expanding from south were found to do well along with cold‐temperate stocks currently inhabiting below‐optimal temperatures in the northern subregion.

Large-scale patterns in community structure of benthos and fish in the Barents Sea - Edda Johannesen; Lis Lindal Jørgensen; Maria Fossheim; Raul Primicerio; Michael Greenacre; Pavel A. Ljubin; Andrey V. Dolgov; Randi B. Ingvaldsen; Natalya A. Anisimova; Igor E. Manushin (Polar Biology, 2017)

Diet of 0-group stages of capelin (Mallotus villosus), herring (Clupea harengus) and cod (Gadus morhua) during spring and summer in the Barents Sea - Torstein Pedersen; Maria Fossheim (Marine Biology, 2008)